OPTIMIZING RAW MATERIAL INVENTORY USING ECONOMIC ORDER QUANTITY (EOQ) METHOD IN BOMBAY BAKERY - Hannum, Syaripah; Ahyaningsih, Faiz; Nasution, Hamidah (ZERO: Jurnal Sains, Matematika dan Terapan, 2023)
Bombay Bakery is a bakery that operates in the field of bread production. Various raw materials used in bread production include wheat flour, butter, sugar, bread improver, eggs and so on. This research aims to determine the optimal order quantity of raw materials each time an order or purchase is made, for the Reorder Point and for the total cost of raw material inventory using the Economic Order Quantity (EOQ). Data collection techniques were carried out by means of library studies and field research. The data analysis technique used is quantitative data analysis technique. Based on perhi analysisThe profit was obtained by ordering or purchasing 659 Kg of raw materials for wheat flour, 37 Kg of butter, 102 Kg of sugar, 3 Kg of bread improver, and 11 eggs with a reorder point for wheat flour raw materials of 501 Kg, 24 Kg of butter, 65 Kg of sugar, 1 Kg of bread leaven, and 8 pieces of eggs. With total costs using company policy of IDR 22,740,233.- while using the Economic Order Quantity (EOQ) model it is IDR 12,761,888.-  so that using the Economic Order Quantity (EOQ) model is more effective in saving raw material inventory costs